PROBLEMATIKA PELAKSANAAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 100/PUU-XI/2013 DALAM MENDUDUKKAN PANCASILA SEBAGAI DASAR NEGARA - Udiyo Basuki; Abdul Kadir Jaelani (Universitas Slamet Riyadi, 2018)
In the legislative system, Pancasila is a basic norm (staatsfundamental), which successively then verfassungnorm UUD 1945, grundgezetznorm or MPR provisions, and gezetznorm or the Act. But in reality, Pancasila is equalized and equated with the 1945 Constitution, the Unitary State of the Republic of Indonesia, Bhinneka Tunggal Ika, which is then referred to as the Four Pillars of Nation and State. The Constitutional Court as the constitution gatekeeper institution returns the position of the Pancasila as the state foundation through the Decision of the Constitutional Court Number 100/PUU-XI/2012. The decision is part of the implementation of the authority of the Constitutional Court which has 4 (four) authorities and 1 (one) obligation as stipulated in Article 24C paragraph (1) and paragraph (2) of the 1945 Constitution. In addition to being a guardian of democracy ) The Constitutional Court is also the Protector of the state's foundation and legal source.